Efektivitas layanan informasi terhadap sikap remaja mengenai obat PCC (paracetamol, cafein, dan carisoprodol) - Fitriyanti, Evi (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2018)
This study aims to determine how the contribution of information services in predicting adolescent attitudes towards PCC drugs (Paracetamol, Cafein, and Carisoprodol), this study uses a quantitative method with a regression analysis approach that aims to find out how much effect the information service provides (as an independent variable) and adolescent attitudes towards PCC (as the dependent variable). This research is to be able to meet the need for information, through the provision of information services, it is expected that service participants will understand the dangers of drug abuse and distribution of PCC and take part in prevention activities to be able to create a conducive environment and run an effective daily life. The results showed that there was a significant change in adolescent attitudes about PCC drugs